Creation of Realistic Appearing Simulated Patient Cases Using the INTERNIST-1/QMR Knowledge Base and Interrelationship Properties of Manifestations - Parker, R. C.; Miller, R. A. (Methods of Information in Medicine, 1989)
The Internist-1/0uick Medical Reference (OMR) knowledge base (KB) describes the clinical manifestations of some 600 diseases in the domain of internal medicine. This KB, while not representing deep causal modelling of disease processes, is nonetheless effective iri providing medical diagnostic assistance through the OMR medical decision support system. One potential application ofthis extensive KB is the generation of simulated patient cases for use in educating health professionals. However, the “flat” KB is not adequate for this because the clinical manifestations used in the disease descriptions are not mutually independent. While it is theoretically possible to construct disease descriptions which embody pathophysiologic mechanisms of disease causality, it is not practical from the standpoint of resource utilization. Short of constructing a causal knowledge base, the authors herein describe the generation of realistic appearing simulated patient case data using existing information in the knowledge base. This existing information in the KB is in the form of properties which represent a shallow form of interrelationships of the manifestations. The authors conclude that this ability to generate simulated cases represents another view in which to look at an extensive knowledge base, as well as having application to constructing intelligent tutoring systems for health professionals in training.
Keywords: Computer Simulation; Computer-Based Problem Solving; Knowledge Bases, Health Education